Schlafapnoetherapie mit einer neuartigen Rückenlage-Verhinderungs-Weste = Treatment of obstructive sleep apnea with a new vest preventing the supine position - Maurer, Joachim T.; Stuck, Boris; Hein, Gerhard; Verse, Thomas; Hörmann, Karl (Deutsche medizinische Wochenschrift, 2003)
Thieme E-Books & E-Journals